2018
DOI: 10.1186/s12939-018-0814-0
|View full text |Cite
|
Sign up to set email alerts
|

Setting the agenda for nurse leadership in India: what is missing

Abstract: BackgroundCurrent policy priorities to strengthen the nursing sector in India have focused on increasing the number of nurses in the health system. However, the nursing sector is afflicted by other, significant problems including the low status of nurses in the hierarchy of health care professionals, low salaries, and out-dated systems of professional governance, all affecting nurses’ leadership potential and ability to perform. Stronger nurse leadership has the potential to support the achievement of health s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 23 publications
0
30
0
2
Order By: Relevance
“…Varghese et al . [ 35 ] reported that the absence of quantifiable evidence on the nurse leadership crisis and the treatment of nursing reforms as a “second class” issue were found to negatively influence perceptions of the validity of nurse leadership reform. The present investigation confirms that nurses have a poor mental health which can affect patient safety, quality of care, and the profitability of the organizations [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Varghese et al . [ 35 ] reported that the absence of quantifiable evidence on the nurse leadership crisis and the treatment of nursing reforms as a “second class” issue were found to negatively influence perceptions of the validity of nurse leadership reform. The present investigation confirms that nurses have a poor mental health which can affect patient safety, quality of care, and the profitability of the organizations [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, though nurses have exhibited competence in leadership required for strengthening of health care in various other country, lack of opportunities or representation in India causes discouragement. The strong opposition by doctors opposing inclusion of nurses in the Medical Termination of Pregnancy (Amendment) Bill in 2014 reflects the attitude towards the nursing cadre [10,11]. However, evidences across the globe highlight the benefits gained through the advancement of nursing cadre through nurse practitioners degree.…”
mentioning
confidence: 99%
“…This examination of organisational perspectives and theories surrounding the integration of these elements leads to the understanding that different partnering types are likely to interact with some elements more than others ( Figure 6). For example, a partnership synergy theory suggests that certain characteristics are intrinsic to partnerships, namely leadership, administration and management, governance and efficiency; and these elements are similar to the domains of financial and contractual mechanisms, leadership and governance and service and care model design from the framework herein (Lasker et al, 2001). As such, one could argue that partnering interventions largely exerts their forces of change through changes to service and care model design, leadership, governance and financial and contractual mechanisms, and that subsequent changes to IT systems, culture and workforce occur as knock-on effects.…”
Section: Culturementioning
confidence: 99%